Caliban and the Yankees : Trinidad and the United States occupation - Neptune, Harvey R., 1970- (University of North Carolina Press, 2007)
In a compelling story of the installation and operation of U.S. bases in the Caribbean colony of Trinidad during World War II, Harvey Neptune examines how the people of this British island contended with the colossal force of American empire-building at a critical time in the island's history. The U.S. military occupation between 1941 and 1947 came at the same time that Trinidadian nationalist politics sought to project an image of a distinct, independent, and particularly un-British cultural landscape. The American intervention, Neptune shows, contributed to a tempestuous scen.